Research on the optimization of public health emergency response systems in higher education institutions - Wang, Ping; Yao, Xueli; Yu, Jie; Chen, Yan; Huang, Fangfang; Pan, Xinjuan; Zhang, Yingjian (Frontiers in Public Health, 2026)
ObjectivesIn response to the frequent occurrence of public health emergencies in universities and the inadequacies in prevention and control systems, this study aims to establish a scientific and effective early warning mechanism and emergency management system to enhance universities' response capabilities and ensure the health and safety of teachers and students.MethodsA combination of literature review and empirical questionnaire surveys was adopted. Domestic and international literature on emergency management in universities was systematically analyzed to identify existing issues. Based on questionnaire data from 556 students at a university in Henan, their awareness levels, psychological states, and information acquisition channels regarding public health emergencies were assessed. Practical cases were also incorporated to validate effectiveness.ResultsWhile current early warning mechanisms and emergency management systems have seen significant improvements, gaps remain. This study summarizes recent issues and actionable measures in a review format, supplemented by practical measures from a specific university, providing theoretical support for addressing public health emergencies in universities. This further safeguards the physical and mental well-being of teachers and students, ensuring social harmony and stability.